What does success look like for air quality policy? A perspective. (30th October 2020) - Monks, Paul S.; Williams, Martin L.
Abstract : This paper explores the drivers and role of science in air quality policy over the last 100 years or so. Case studies on the smogs of Los Angeles and London, acid rain, health impacts of particulate matter, diesel and lead in fuel are used to explore the drivers and models for the interaction of science, evidence and air quality policy. It suggests there are two phases to air quality mitigation, the first driven by the air quality emergency as the pollution is visible and the effects can be relatively obvious and the second driven by science that is directed towards continuous improvement. A critical element of the 'science phase' is the evidence base, the models of evidence-based and -informed policy-making are explored with the conclusion that it is optimal when guided by the ideal of co-creation of knowledge and policy options between scientists and policy-makers. The future and wider drivers for air quality are detailed with a number of key areas for 'success' indicated as important for air quality policy development such as continuous improvement. Overall, we find there is tension between two factors: the ambition to reduce emissions, improve air quality and reduce the impacts on public health and the environment on one hand, and questions of cost, technical feasibility and societal acceptability on the other. This article is part of a discussion meeting issue 'Air quality, past present and future'.